AN INTEGRATED TECHNIQUE IN ACHIEVING THE CONFIDENTIALITY, INTEGRITY AND ROBUSTNESS FOR BIG DATA TRANSMISSION - BHATTACHARJEE, SHILADITYA (2017)
The data confidentiality, integrity, and data loss are issues during transmission due to inadequate security scheme. These issues become more critical in the big data transmission due to its own individual overhead. Moreover, multiple executions of distinct security algorithms for maintaining confidentiality and integrity reduce Throughput and add large number of additional bits as security overheads which hamper the robustness against data loss. Conversely, an efficient compression technique minimizes the data confidentiality as it eliminates the redundant data during compression. However, the current literature fails to suggest any security mechanism which can solve all these issues in a combinatorial way. Henceforth, this research addresses these security issues collectively without negatively affecting each other. It increases confidentiality and offers a backup for accidental data loss by combining Simplified Encryption Standard (SDES) and an advanced pattern generation technique which uses a unique pattern generation table. A novel dual round of error control technique has been incorporated to maximize the data integrity by addressing any number of transmission errors. A new compression technique is included to enhance robustness against data loss by producing high compression efficiency and resistance against transmission errors. Confidentiality and integrity are further enhanced by integrating an advance audio steganography which uses a distinctive sample selection for hiding bits. Experiments are conducted using standard Calgary Corpuses, text files (up to 1 TB), and audio files to validate the objectives. The proposed integrated technique offers higher confidentiality level by producing higher Signal to Noise Ratio (60.79-60.91 dB) and Frequency Difference (0.37-0.27 Hz) than other related security techniques. It can protect different security attacks by offering higher Avalanche Effects (76.2%) and Entropy Value (7.77). It also offers higher integrity and robustness against data loss by contributing lower percentages of Information Loss (0.004-0.0009%) and Uncorrectable Error Rate (0.0096-0.0094%).